Do you look where I look? Attention shifts and response preparation following dynamic social cues - Frouke Hermens; Robin Walker (Bern Open Publishing, 2012)
Studies investigating the effects of observing a gaze shift in another person often apply static images of a person with an averted gaze, while measuring response times to a peripheral target. Static images, however, are unlike how we normally perceive gaze shifts of others. Moreover, response times might only reveal the effects of a cue on covert attention and might fail to uncover cueing effects on overt attention or response preparation. We therefore extended the standard paradigm and measured cueing effects formore realistic, dynamic cues (video clips),while comparing response times, saccade direction errors and saccade trajectories. Three cues were compared: A social cue, consisting of a eye-gaze shift, and two socially less relevant cues, consisting of a head tilting movement and a person walking past. Similar results were found for the two centrally presented cues (eye-gaze shift and head tilting) on all three response measures, suggesting that cueing is unaffected by the social status of the cue. Interestingly, the cue showing a person walking past showed a dissociation in the direction of the effects on response times on the one hand, and saccade direction errors and latencies on the other hand, suggesting the involvement of two types of (endogenous and exogenous) attention or a distinction between attention and sacadic response preparation. Our results suggest that by using dynamic cues and multiple response measures, properties of cueing can be revealed that would not be found otherwise.